Gracilins: Spongionella-derived promising compounds for Alzheimer disease. (June 2015) - Leirós, Marta; Alonso, Eva; Rateb, Mostafa E.; Houssen, Wael E.; Ebel, Rainer; Jaspars, Marcel; Alfonso, Amparo; Botana, Luis M.
Abstract: Alzheimer disease (AD) is a neurodegenerative pathology that is strongly linked with oxidative stress and mitochondrial dysfunction. The unclear origin of AD lead researchers to study several drug targets and it has been proposed that a multi-target drug would be a more promising candidate. Gracilins are sponge-derived diterpenoid compounds that have been described to act as antioxidants through mitochondrial targeting and through the induction of Nrf2 translocation. In this work gracilin H, A and L and tetrahydroaplysulphurin-1 have been studied in two neuroblastoma cellular models. First the BE(2)-M17 cell line has been used as a model for APP metabolism studies and next, SH-SY5Y-TMHT441 cells were used for AD drugs screening targeting tau phosphorylation. In vitro assays showed that gracilins were able to inhibit BACE1, reduce tau hyperphosphorylation and inhibit ERK. These positive results lead us to test gracilin H and L in 3xTg-AD mice. After chronic intraperitoneal treatments, a preliminary behavioral test pointed a positive trend on learning and spatial memory of mice treated with these compounds. Moreover in vivo assays confirmed the previous results. Amyloid-β42 and hyperphosphorylated tau levels were decreased after treatments and the ERK inhibition was also observed. This research highlights new bioactivities for gracilins, such as BACE1 and ERK inhibition, and provides more evidence for their potential therapeutic application in neurodegenerative diseases due to their multi-target activities, especially in AD. Highlights: Only gracilin L produces in vitro BACE1 inhibition in vitro . Gracilins reduce tau phosphorylation through ERK inhibition in vitro . Preliminary studies in 3xTg-AD mice with garcilin H and L ameliorate cognition. Gracilin H and L reduces Aβ42 and phosphorylated tau levels in vivo . ERK is inhibited by gracilins in brains lysates of 3xTg-AD mice.